EVALUASI KINERJA PENGAWASAN PENGELOLAAN KEUANGAN DAERAH DIUKUR DARI PERATURAN BPKP NO. 16 TAHUN 2015 PADA INSPEKTORAT KABUPATEN MINAHASA SELATAN - Lumempow, Figy; Elim, Inggriani; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Supervision over the implementation of local government is done by Provincial Inspectorate and District / City. Supervision over the implementation of regional government is a mandate from the provisions of Article 378 of Law Number 23 Year 2014 on Regional Government. The purpose of this study is to evaluate the performance of supervision and management of regional finances at the Inspectorate of South Minahasa Regency is in accordance with BPKP Regulation no. 16 Year 2015, know what is done in overcoming obstacles on the performance of supervision of local financial management at the Inspectorate of South Minahasa District. The method used in this research is descriptive qualitative method. The results showed that the performance of supervision of regional financial management at Inspectorate of South Minahasa Regency not yet in accordance with Regulation of BPKP. 16 Year 2015. This is due to several obstacles, among others: the APIP enhancement capability assessment program, the Inspectorate of South Minahasa Regency is still considered at the lowest level so that the impact on APIP performance has not been effective.Keywords: Evaluation, Performance, Monitoring, Financial Management